2015
DOI: 10.1016/j.ejcdt.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weight reduction on obese patients with COPD and bronchial asthma

Abstract: There is a link between obesity and both, asthma and COPD. Aim of the work: To study effect of weight reduction on pulmonary function tests of obese COPD and bronchial asthma patients.Subjects and methods: 2 groups were included, group(G)I, 30 obese COPD and GII 30 obese bronchial asthma patients. Pulmonary function tests were done to all participants before and after weight reduction.Results: GI showed increased FRC, ERV and RV significantly, IC was significantly decreased and GII showed increased FEV 1 , FVC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…A more controversial explanation for increased dyspnea in obesity is its association with increased oxidative stress, which plays an important inflammatory role [ 30 ]. It has been demonstrated over time that weight reduction significantly improves the respiratory symptoms exhibited by obese patients [ 31 34 ].…”
Section: Extrathoracic Mimickers Of Asthmamentioning
confidence: 99%
“…A more controversial explanation for increased dyspnea in obesity is its association with increased oxidative stress, which plays an important inflammatory role [ 30 ]. It has been demonstrated over time that weight reduction significantly improves the respiratory symptoms exhibited by obese patients [ 31 34 ].…”
Section: Extrathoracic Mimickers Of Asthmamentioning
confidence: 99%
“…These patients may be at increased risk of poor outcomes and also emphasise the role that weight reduction programmes may have on health outcomes in obese adults with COPD. 33 , 34 The association between prior oral antibiotic prescription and poor outcomes may relate to the diverse nature of exacerbations 35 and warrant an investigation into the extent to which post-consultation outcomes are differentially associated with presenting and clinical variables by phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the relationship between daily physical activity level and functional exercise capacity is emphasized, but results are inconsistent whether this relationship is strong or weak (Fastenau, van Schayck, Gosselink, Aretz, & Muris, ; Zwerink, van der Palen, van der Valk, Brusse‐Keizer, & Effing, ). However, it is reported that in patients with COPD, obesity has an adverse effect on functional exercise capacity, and reduces FVC and FEV1 (Gagnon et al, ), but there might be an increase in static lung volume if there is weight loss (El‐Shafey & El‐Deib, ). In the current study, the obese patients' respiratory parameters improved after the regular walking program compared with baseline, and to those of the participants in the other 2 groups.…”
Section: Discussionmentioning
confidence: 99%